Organic Electronics for Artificial Touch. Issue 9 (September 2018) - Black, Christopher; Darie, Radu; Borton, David
Abstract : Artificial restoration of touch is an active area of research in neuroprosthetics. However, most approaches do not consider emulating the biological machinery they intend to replace. Recently, Kim et al . proposed a bioinspired artificial touch transducer that closely mimics the behavior of natural sensory afferents.